The consequences of task-supported language teaching via social media on academic engagement, emotion regulation, willingness to communicate, and academic well-being from the lens of positive psychology - Alazemi, Asmaa Falah Theiyab; Gheisari, Asma; Patra, Indrajit (Asian-Pacific Journal of Second and Foreign Language Education, 2023)
Although TBLT has been the subject of many prior studies, no research has addressed the impact of TBLT through social media (SM), specifically the Telegram app, on academic engagement, emotion regulation, willingness to communicate (WTC), and academic well-being. To reach this goal, a convenience sampling method was used to select 58 Iranian intermediate EFL learners out of 83 based on their Oxford Quick Placement Test performance. The selected learners were randomly assigned to the control group (CG) and experimental group (EG). Pretests were conducted to measure both groups’ academic engagement, emotion regulation, WTC, and academic well-being. During the treatment, the EG received treatment using the Telegram app and the LMS, while the CG only utilized the LMS without any social media assistance. After the treatment, posttests were administered to evaluate the performance of both groups. The results of the data analysis revealed a significant difference in the posttest scores of the EG and CG. The EG demonstrated superior outcomes ( p < 0.05) regarding academic engagement, emotion regulation, WTC, and academic well-being, indicating the effectiveness of incorporating Telegram alongside the LMS. Thus, this study demonstrated that utilizing the Telegram app with an LMS can significantly enhance EFL learners’ WTC, academic engagement, well-being, and emotion regulation. The findings suggest that EFL students can utilize the Telegram app to improve their English language skills outside of traditional classroom settings. Furthermore, using social media platforms like Telegram can facilitate self-study and transform the role of students. It provides EFL students with easy and rapid access to global information. The study concludes with implications, limitations, and suggestions for future research.